Dipeptiven® improves kidney pathology in a rat model of chronic kidney disease. (June 2019) - Bothe, Melanie K.; Berressem, Dirk; Abele, Rosa; Topp, Heinrich; Alteheld, Birgit; Stehle, Peter; Harleman, Johannes; Westphal, Martin; Stover, John F.
Summary: Background & aims: Administration of glutamine in patients with renal dysfunction is considered to be potentially adverse. In a rat model of moderate kidney dysfunction dose-dependent effects of intravenous alanyl-glutamine infusion on possible biochemical and histological signs of toxicity were investigated. Methods: Rats with renal dysfunction resulting from 5/6 nephrectomy received a 9 days continuous intravenous infusion of either saline or 0.5 g/kg/day or 3.0 g/kg/day alanyl-glutamine (Dipeptiven ® ) or 3.0 g/kg/day alanine. Dose-dependent effects on kidney and other organs were assessed by analyzing blood levels of creatinine, ammonia, urea, ALT, AST, ALP, pH, pO2, pCO2, glutamine, and histopathology. Results: Continuous intravenous infusion of 3.0 g/kg/day alanyl-glutamine increased plasma glutamine concentrations up to 60% without aggravating the underlying kidney injury. In contrast, the morphology of the kidneys was improved due to reduced glomerulosclerosis and tubular proteinaceous casts. An increase in plasma urea concentrations observed in the 3.0 g/kg/day alanyl-glutamine group only was not associated with worsening of the phenotype. Conclusions: Continuous intravenous infusion of alanyl-glutamine at 0.5 and 3.0 g/kg/day up to 9 consecutive days is safe in a rat model of chronic moderate kidney dysfunction and improved the renal morphology by reducing glomerulosclerosis and tubular proteinaceous casts. In these animals a decreased incidence and severity of chronic progressive nephropathy was observed compared to the saline and alanine treated animals.